Case Study: Influence of Three Gorges Reservoir Impoundment on Hydrological Regime of the Acipenser sinensis Spawning Ground, Yangtze River, China - Zhou, Yinjun; Li, Zhijing; Yao, Shiming; Shan, Miner; Guo, Chao (Frontiers in Ecology and Evolution, 2021)
After the construction of the Three Gorges Dam (TGD) in China, the downstream has been affected by the reduction in sediment discharge and regulation of flow processes, which have resulted in severe scouring and changes hydrological regime. Consequently, the spawning ground of Chinese sturgeon distributed along the downstream Yichang reach could be affected. This study examined the effects of TGD on the streamflow, sediment load and channel morphology downstream based on in situ measured data. Results showed that, after the impoundment of the TGD, sediment load at the downstream Yichang hydrological station decreased significantly, and the Yichang reach continued to be scoured. The distribution of erosion was uneven, and the scouring mainly occurred in the branching channels. The channel gradient and riverbed roughness increased with the erosion of the river cross section. After more than 10 years of erosion, the riverbed scouring and armouring in the Yichang reach was basically completed, thus we expected that the spawning grounds of Chinese sturgeon could be retain as the riverbed tends to be stable. The findings in this work have implications in the protection of the critically endangered Chinese sturgeon.